On dying in a city gate: implications in the deaths of Eli, Abner and Jezebel - Quine, Cat (Sage Publications, 2016)
Previously one could easily find works on the archaeology or biblical study of cities, defences, temples and houses, but in the past year, two publications on city gates have caught the eye. What follows is concerned with applying these new conversations about the role and function of ancient Israelite city gates to the biblical texts in a socio-historical manner, and in doing so, it draws attention to the way in which the author in 1 & 2 Samuel and 2 Kings uses gates as a literary device.